Europæisk offentlighed i danske medier – Danmark som foregangsland for udviklingen af en transnational politisk journalistik? - Mark Ørsten (Journalistica, 2006)
This article focuses on the Europeanization of the Danish news media. Europeanization of media content refers to two central criteria: a) an increased focus on European themes and actors, and b) an evaluation of theses themes and actors from a connation state dominated point of view. According to such criteria, recent studies across Europe, have documented a significant level of overall Europeanization of Danish media at the level of media content. This article compares the results of some of the most recent studies of Europeanization and tries to answer the question of what makes Denmark a best-case example, when it comes to Europeanization of the news media.